Husband Support and Coping Stress on Exclusive Breastfeeding in Primipara - Simanjuntak, Roganda; Wardani, Diadjeng Setya; Indrawan, I Wayan Agung; Hinisa, Fariha Nuzulul (JURNAL INFO KESEHATAN, 2024)
Breastfeeding is the best strategy to ensure optimal growth and development for infants. Social support, fatigue, and stress are the main factors that hinder breastfeeding for primiparous mothers. This cross-sectional study analyzes husband support and coping stress of exclusive breastfeeding for primiparous mothers with a quantitative approach. The samples were 70 respondents taken with a total sampling technique. The research instruments were the husband support questionnaire and coping strategies inventory. The researchers analyzed the data with chi-square and multiple logistic regression. The results found 48 (68.5%) mothers with excellent husband support and exclusive breastfeeding. Meanwhile, mothers with excellent husband support but without exclusive breastfeeding were 18 respondents (25.71%). The results of statistical tests with a significance level of 5% obtained a sig value (p-value) of husband support (p=0.002) and coping stress p=0.000. The result indicates a correlation between husband support and coping stress on exclusive breastfeeding with OR value = (3.667). On the other hand, mothers with excellent husband support could provide exclusive breastfeeding 4 times higher than those with poor husband support. Husband support and coping stress affect exclusive breastfeeding of primiparous mothers in the employed area of Puskesmas Dinoyo Malang City. Coping stress is the dominant factor influencing exclusive breastfeeding in primiparous mothers in the employing area of Puskesmas Dinoyo Malang City. The research recommends public health centers improve programs that support maternal care in helping to improve skills in managing stress, on exclusive breastfeeding both at the public health center, the integrated public health service, and the auxiliary health center.